2013
DOI: 10.1002/asna.201211713
|View full text |Cite
|
Sign up to set email alerts
|

The opacity of spiral galaxy disks: IX. Dust and gas surface densities

Abstract: Our aim is to explore the relation between gas, atomic and molecular, and dust in spiral galaxies. Gas surface densities are from atomic hydrogen and CO line emission maps. To estimate the dust content, we use the disk opacity as inferred from the number of distant galaxies identified in twelve HST/WFPC2 fields of ten nearby spiral galaxies. The observed number of distant galaxies is calibrated for source confusion and crowding with artificial galaxy counts and here we verify our results with sub-mm surface br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 113 publications
(163 reference statements)
0
7
0
Order By: Relevance
“…The faceon optical depths found are typically smaller than one at optical wavelengths, indicating that the entire galaxy disc would be almost transparent when seen face-on. This result is somewhat in contradiction to the spiral disc transparency measurements using either the number of background galaxies (Holwerda et al 2005a(Holwerda et al , 2007b or overlapping galaxy pairs (Domingue et al 2000;Keel & White 2001a,b;Holwerda et al 2009Holwerda et al , 2013. These studies find that spiral arms are opaque and discs gradually become optically thick towards the galaxy's centre.…”
Section: Introductionmentioning
confidence: 56%
“…The faceon optical depths found are typically smaller than one at optical wavelengths, indicating that the entire galaxy disc would be almost transparent when seen face-on. This result is somewhat in contradiction to the spiral disc transparency measurements using either the number of background galaxies (Holwerda et al 2005a(Holwerda et al , 2007b or overlapping galaxy pairs (Domingue et al 2000;Keel & White 2001a,b;Holwerda et al 2009Holwerda et al , 2013. These studies find that spiral arms are opaque and discs gradually become optically thick towards the galaxy's centre.…”
Section: Introductionmentioning
confidence: 56%
“…Indeed, direct observations of galaxies have indicated that the intrinsic nature of dust in galaxies is highly variable, depending on multiple factors such as morphology and environment (see, e.g. , White et al 2000;Keel & White 2001;Holwerda 2005;Holwerda et al 2013a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The face-on optical depths found are typically smaller than one at optical wavelengths, indicating that the entire galaxy disc would be almost transparent when seen face-on. This result is somewhat in contradiction to the spiral disc transparency measurements using either the number of background galaxies (Holwerda et al 2005a(Holwerda et al , 2007b or overlapping galaxy pairs (Domingue et al 2000;Keel & White 2001a,b;Holwerda et al 2009Holwerda et al , 2013. These studies find that spiral arms are opaque and discs gradually become optically thick towards the galaxy's centre.…”
Section: Introductionmentioning
confidence: 56%